Komunikasi, Informasi dan Edukasi pada Kasus Leukoplakia Homogen - Naviatullaily Yarsiska; Shinta Amalia Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Homogeneous leukoplakia is a mucosal lesion that is mostly white in color with a thin, flat surface that cannot be scraped off, most commonly found on the buccal mucosa, tongue, and floor of the mouth. In contrast to non-homogeneous leukoplakia, which appears white and red, and is nodular, speckled, or granular, non-homogeneous leukoplakia has a higher risk of malignant transformation. However, homogeneous leukoplakia is more commonly encountered than the non-homogeneous type. This article aims to report the management and implementation of communication, information, and education (CIE) in a suspected case of homogeneous leukoplakia in a 20-year-old woman. The patient presented to the Soelastri Dental and Oral Hospital in Surakarta with a complaint of a white patch on the tip of her tongue that had been present for six months. The patient had previously undergone scraping with gauze and betadine and was given antibiotics and mouthwash, but there was no significant change. Intraoral examination revealed a white patch on the dorsum of the tongue with a velvety surface, well-defined borders, asymptomatic, soft consistency, and rough texture. The management of this case included a thorough oral cavity examination, as well as providing detailed CIE about the condition experienced by the patient, including the importance of eliminating risk factors and reducing the likelihood of malignant transformation. The patient was also advised to undergo supportive testing, including biopsy, to confirm the diagnosis. In conclusion, homogeneous leukoplakia is a lesion that is mostly white, thin, flat, and cannot be scraped off. Management focuses on appropriate CIE, managing the existing lesions, eliminating causal factors, and monitoring the risk of malignant transformation. The implementation of CIE is effective in improving patient understanding and supporting patient involvement in managing the condition, thereby minimizing complications and long-term risks.